Toni Morrison : An Ethical Poetics - Christiansë, Yvette (Book collections on Project MUSE., 2013)
This book situates Toni Morrison as a writer who writes about writing as much as about racialized, engendered, and sexualized African American, and therefore American, experience. In foregrounding the ethics of fiction writing, the book resists any triumphalist reading of Morrison's achievement in order to allow the meditative, unsettled, and unsettling questions that arise throughout her long labor at the nexus of language and politics, where her fiction interrogates representation itself. Moving between close reading and critical theory, the author reveals the ways in which Morrison's primary engagement with language has been a search for how and what language is made to communicate, and for how and what speaks in and from generation to generation. There is no easy escape from such legacy, no escape into a pure language free of the burdens of racialized agendas. Rather, there is the example of Morrison's commitment to writerly, which is to say readerly, wakefulness.--description from publisher's website.